Heuristics and Heterogeneity in Health Insurance Exchanges: Evidence from the Massachusetts Connector - Ericson, Keith Marzilli; Starc, Amanda (American Economic Review, 2012)
We examine heuristic decision rules in consumer choice on health insurance exchanges using data from the Massachusetts Connector. Consumers may have difficulty making optimal choices in a complex environment. The heuristic “choose the cheapest plan” is suggested by the decision context, previous research, and the data: about 20% of enrollees choose the cheapest plan possible. We find evidence of this heuristic in many models, but while heuristics may play a role, preference heterogeneity is also important. Our most flexible models find an insignificant heuristic effect. In part because holding context fixed, this heuristic is observationally equivalent to extreme price sensitivity.